Anaerobic Cr(VI) Bioaccumulation: Application to Industrial Wastewater and Soil Matrices in Jordan - H. Arar, Sharif; A. Abu Eid, Rasha; K. Fayyad, Manar (Asian Journal of Chemistry, 2015)
Chromium(VI) in the form of CrO42- or Cr2O72- is known to be very toxic causing cell mutation and imposing serious health and environmental impact that mandates the removal of this toxic element. In this study, an investigation of the anaerobic Cr(VI) bioaccumulation by microbial biomass originated from wastewater influent utility was conducted and optimized for different conditions and parameters. These parameters include Cr(VI) initial concentration, nutrient type and concentration, temperature and pH. The obtained results indicated that the bioaccumulation process involves an adsorption, coupled with metabolic reduction mechanism. This bioaccumulation varies inversely with pH, proportionally with temperature, proportionally with Cr(VI) initial concentration in the presence of sucrose as nutrient; and inversely with Cr(VI) initial concentration when using glycerol and sodium acetate as nutrients. The optimum conditions for best removal of Cr(VI) were 11 ppm of Cr(VI) initial concentration, 20 mM sucrose, at 60 °C and pH = 1. The optimized conditions were applied to industrial wastewater sample and soil sample from Arab Aluminum Industries plant in Jordan. The percentages of removal of Cr(VI) were 91 and 93 %, respectively over 8 days at 25 °C making it a potential efficient and low cost remediation method for Cr(VI) removal.